Artificial Intelligence Dalam Pembelajaran Nahwu Secara Mandiri - Rishanda, Aflah Tamami; Koderi, Koderi; Ghazi, Fachrul; Mizan, Ahmad Nur (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This article aims to explore artificial intelligence technology for learning Nahwu independently. Nahwu is a branch of Arabic language learning focused on studying the structure of Arabic grammar. The type of research used is a literature review with a qualitative approach. Data analysis involves content analysis of articles sourced from Scopus, Google Scholar, CrossRef, and conference proceedings. The results of this study explain how artificial intelligence technology can be utilised, its benefits and challenges, and the approaches to using it for independent Nahwu learning by teachers and learners. Research has proven that artificial intelligence technology revolutionizes education and enhances learning quality. Artificial intelligence technology adjusts the learning speed of each nahwu learner and assists teachers in preparing nahwu learning materials. Artificial intelligence technology can solve the problem of nahwu learning independently. The use of artificial intelligence technology, such as ChatGPT, Chatsonic, the Telegram application, and the Breadth First Search algorithm, can help improve Nahwu learning independently. However, its use can lead to negative impacts, such as reduced social interaction, scattered learner data, and loss of physical classroom environment experience that supports affective aspects of learning. Therefore, it is necessary to have the role of teachers in equipping, supervising, and evaluating the use of artificial intelligence technology for Nahwu learners.